2013
DOI: 10.3892/ijo.2013.1799
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of JARID1B induces cellular senescence in human colorectal cancer

Abstract: The global incidence of colorectal cancer (CRC) is increasing. Although there are emerging epigenetic factors that contribute to the occurrence, development and metastasis of CRC, the biological significance of epigenetic molecular regulation in different subpopulations such as cancer stem cells remains to be elucidated. In this study, we investigated the functional roles of the H3K4 demethylase, jumonji, AT rich interactive domain 1B (JARID1B), an epigenetic factor required for the continuous cell growth of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 25 publications
4
46
0
Order By: Relevance
“…SKP2 deficiency induces cellular senescence in contexts of oncogenic insults [8], and recently JARID1B is associated with cellular senescence in colorectal cancer and retinoblastoma cells [38, 39]. We reasoned that K63-linked ubiquitination of JARID1B accumulated in nucleolus may contribute to SKP2-deficient induced cellular senescence.…”
Section: Resultsmentioning
confidence: 99%
“…SKP2 deficiency induces cellular senescence in contexts of oncogenic insults [8], and recently JARID1B is associated with cellular senescence in colorectal cancer and retinoblastoma cells [38, 39]. We reasoned that K63-linked ubiquitination of JARID1B accumulated in nucleolus may contribute to SKP2-deficient induced cellular senescence.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, others have demonstrated that KDM6B acts as a tumor suppressor by regulating p53 nuclear stabilization (71). In colorectal cancer, depletion of KDM5B induced cellular senescence (72). In breast cancer, the methyltransferase G9a plays a critical role in the epigenetic regulation of epithelial-mesenchymal transition (73).…”
Section: Discussionmentioning
confidence: 99%
“…Ohta et al (2013) demonstrated that JARID1B/KDM5B may play a role in active chromatin compaction of the p16 promoter, contributing to gene silencing. Therefore, JA-RID1B/KDM5B depletion may lead to p16 activation.…”
Section: Discussionmentioning
confidence: 99%